2005
DOI: 10.1126/science.1118923
|View full text |Cite
|
Sign up to set email alerts
|

Deep Impact: Excavating Comet Tempel 1

Abstract: Deep Impact collided with comet Tempel 1, excavating a crater controlled by gravity. The comet's outer layer is composed of 1- to 100-micrometer fine particles with negligible strength (<65 pascals). Local gravitational field and average nucleus density (600 kilograms per cubic meter) are estimated from ejecta fallback. Initial ejecta were hot (>1000 kelvins). A large increase in organic material occurred during and after the event, with smaller changes in carbon dioxide relative to water. On approach, the spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
248
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 740 publications
(268 citation statements)
references
References 21 publications
10
248
2
3
Order By: Relevance
“…The compact aggregates are assumed to have a fractal dimension , which corresponds to the value when the D p 2.5 maximum compression of fluffy aggregates is attained (Wada et al 2008). Our calculation using the superposition T-matrix method (TMM) showed that the geometric albedo of the compact aggregates is ∼0.04 at visible wavelengths (see Kimura, Kolokolova, & Mann 2003), and this value is identical to the albedo derived from an observation of the T1 surface (A'Hearn et al 2005). We also calculate (the ratio of solar rab ∼ 0.3 diation pressure to solar gravity) for the compact aggregates, using Mie theory with the optical constants deduced from the Maxwell-Garnett mixing rule (MG) (see Mukai et al 1992): This is also consistent with b for high-velocity ejecta within the DI ejecta plume (e.g., Meech et al 2005).…”
Section: Aggregate Modelsupporting
confidence: 63%
See 1 more Smart Citation
“…The compact aggregates are assumed to have a fractal dimension , which corresponds to the value when the D p 2.5 maximum compression of fluffy aggregates is attained (Wada et al 2008). Our calculation using the superposition T-matrix method (TMM) showed that the geometric albedo of the compact aggregates is ∼0.04 at visible wavelengths (see Kimura, Kolokolova, & Mann 2003), and this value is identical to the albedo derived from an observation of the T1 surface (A'Hearn et al 2005). We also calculate (the ratio of solar rab ∼ 0.3 diation pressure to solar gravity) for the compact aggregates, using Mie theory with the optical constants deduced from the Maxwell-Garnett mixing rule (MG) (see Mukai et al 1992): This is also consistent with b for high-velocity ejecta within the DI ejecta plume (e.g., Meech et al 2005).…”
Section: Aggregate Modelsupporting
confidence: 63%
“…Plenty of DI observational results support the standard model: (1) The presence of a dust mantle on T1 is evidenced by a low thermal inertia of the nucleus estimated from its thermal maps (A'Hearn et al 2005).…”
Section: Introductionmentioning
confidence: 73%
“…Furthermore, that lack of overall correlation between H 2 O, CO and CO 2 implies that the outgassing from the nucleus is not correlated, or that CO and CO 2 are not strictly embedded in H 2 O. For Temple 1, material was found in layers and supports the above idea (16). In summary, the coma composition has been measured over many rotational periods of the comet and a wide range of latitudes with high time resolution and compositional detail.…”
mentioning
confidence: 73%
“…Excavation of Tempel 1 by a projectile carried by the Deep Impact spacecraft suggests a nucleus with volatiles hidden below a thin mantle of fine powdery material (A'Hearn et al, 2005). The surface of 67P/ChuryumovGerasimenko is characteristically similar to 9P/ Tempel 1 in terms of its phase function and it is anticipated to have a similar thermal inertia (Lamy et al, 2006).…”
Section: The Comet Ice Modelmentioning
confidence: 99%